A multi wavelength Raman scattering study of defective graphitic carbon materials: The first order Raman spectra revisited. (October 2016) - Couzi, Michel; Bruneel, Jean-Luc; Talaga, David; Bokobza, Liliane
Abstract: The Raman spectra of a number of defected graphitic carbonaceous materials have been recorded using a large panel of laser exciting lines ranging from 1064 to 325 nm. They concern Arkema and Nanocyl multiwall nanotubes, Pyrograph nano filaments, heat-treated glassy carbons and graphite nano platelets. A particular attention was paid on the characteristic spectral range (≈1000–1300 cm −1 ) of the so-called "D4 " band. It is shown that in fact three different components participate to the scattered signal in this spectral range, whose relative intensities depend on the carbon considered. They include the dispersive D″ band, an additional dispersive band denoted D** and a non-dispersive band denoted D*. When considering the different defect-induced double resonance inter-valley scattering processes, and according to symmetry considerations, these components are assigned to phonon modes belonging to different dispersion branches away from the K point of the Brillouin zone in the Γ-K direction (D″), in the K-M direction (D**) and in the very close vicinity of the K point (D*).